Two-Fluid Mixed Magnetoconvection Flow in a Vertical Enclosure - . Prof. J. Prathap Kumar; J.C. Umavathi; B.M Biradar (Journal of Applied Fluid Mechanics, 2012)
The problem of steady, laminar flow and heat transfer of an electrically conducting fluid through vertical channel in the presence of uniform transverse magnetic field is formulated using a two-fluid continuum model. Combined free and forced convection inside the channel is considered. The effects of viscous and ohmic dissipations are included in the energy equation. Both walls are kept either at the same or different temperatures such as isoflux-isothermal and isothermal-isoflux conditions. Governing equations in cartesian co-ordinates are solved analytically using regular perturbation technique to develop the expression for velocity and temperature. Velocity, temperature and Nusselt number are presented graphically. Effects of pertinent parameters, such as Hartmann number, electric field load parameter, viscosity ratio, width ratio and conductivity ratio are determined.